Open thrombectomy and retrograde mesenteric stenting as a treatment for acute in chronic occlusive mesenteric ischemia: A case report. (9th April 2022) - Bruhn, Peter James; Sandholt, Benjamin; Clausen, Caroline; Zetner, Dennis
In this case report, we outline a tailored approach for a complex patient with acute in chronic proximal occlusive mesenteric disease complicated with fresh thrombosis and a heavily calcified aorta, where the standard treatment proved suboptimal. We outline the surgical considerations that ultimately led to performing a hybrid procedure of open thrombectomy combined with retrograde open mesenteric stenting of the superior mesenteric artery. The patient was a 75-year-old male, with a history of severe arteriosclerosis presenting with abdominal pain over 48 h. An initial diagnostic laparoscopy was performed at a local hospital showing signs of mesenteric ischemia. The patient was transferred to a major trauma hospital, where the patient underwent an open thrombectomy combined with retrograde open mesenteric stenting. The patient's intestines showed no signs of necrosis after surgery, and the patient was discharged nine days after surgery. The patient has experienced no complications and was alive at the 90-day follow-up. This case report outlines the clinical information available to the surgeons, leading to their decision of an infrequently used approach in emergency surgery. We believe that hybrid procedures utilizing the strengths of both open and endovascular surgery should be considered in complex patients where standard treatment options are suboptimal. European guidelines state that retrograde open mesenteric stenting should be performed when antegrade stenting fails, utilizing a through-and-through procedure. We believe that in some cases it is beneficial to the patient to use a hybrid approach including retrograde open mesenteric stenting as first line treatment.